Ich und Poseidon - O'Dell, Scott 1898-1989 (Dt. Taschenbuch-Verl., 1993)
While helping her crippled grandfather by diving for sponges from the family boat after the death of her diver father, Alexandra discovers that someone is using their sponges as a hiding-place for smuggled cocaine.
Keywords: Grandfathers -- Fiction; Greek Americans -- Fiction; Smuggling -- Fiction; Sponge fisheries -- Fiction; Griechen; Florida -- Fiction; Florida; Jugendbuch